PENGARUH EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PERUSAHAAN FARMASI YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2015-2018 - Rais R, Muhammad (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
This study aims to analyze the effect of earning per share on the stock prices of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2015-2018 period. The data collection method used is literature study, data is obtained from data collection and information through documents. The data analysis method used is simple linear regression analysis. Based on the results of data testing and discussion, the following conclusions are obtained simultaneously, the Earning Per Share (EPS) variable has an effect on stock prices. This is indicated by a significance above 0.05. So that if there is an increase in Earning Per Share (EPS) it will affect the stock price. And also this shows that Earning Per Share (EPS) is not the only factor that affects stock prices. For advanced researchers, it is better if it is necessary to add other variables that have an influence and do not affect stock returns so that it can be seen which factors have the most influence and are not influential in an effort to increase stock prices.